The Politics of Slavery - Brace, Laura (2018)
Looking at scholarship on both 'old' and 'new' slavery, Laura Brace assesses the work of Aristotle, Locke, Hegel, Kant, Wollstonecraft and Mill, and explores the contemporary concerns of human trafficking and the prison industrial complex to consider the limitations of 'new slavery' discourse.